Characterization of Noise-Induced Hearing Loss related to work in the Southern region of Brazil from 2019 to 2023 (Research, Society and Development, 2025)
Objective: to carry out an epidemiological analysis of Noise-Induced Hearing Loss (NIHL) related to work in Southern Brazil in the time frame from 2019 to 2023. Methodology: this is a quantitative and descriptive study, which used the database of the Notifiable Diseases Information System (SINAN) as a source of information, and data were also filtered according to the following factors: age group, sex, race and year of notification. Results: this study identified the registration of 837 cases of work-related NIHL, in the period analyzed, with emphasis on the State of Rio Grande do Sul, which had the highest number of notifications with 69% (n = 582), while the year of notification with the highest registration of the disease was 2019, with a total of 27% (n = 226) of all notifications. Conclusion: according to this article, it is possible to infer that work-related PAR is a current public health problem in the South and that the typical profile of people with work-related PAR is composed of male individuals, aged between 50 and 64 years old and white. It is also concluded that work-related PAR is a possible underreported disease in the region, and there is a need for more effective reporting strategies for a greater epidemiological understanding of the disease.